Literature Review: Use of the Taguchi Method for Quality Improvement: Literature Review: Penggunaan Metode Taguchi untuk Peningkatan Kualitas - Setyo Pradana, Eka; Sulistiyowati, Wiwik (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
Literature Review articles from a collection of various research journals using the Taguchi method in quality development taken from Scopus data of 2,000 documents data from 2000 to 2022. Scopus is an index of scientific literature to provide accurate information about the metadata of each scientific article individually, including publication data, abstracts, references, etc. Using this Scopus data can provide a broad overview of the use of the Taguchi method for quality development in all fields in detail. With this software, data analysis can be generated using the Taguchi method in any field. As well as in engineering as much as 32.2% (14,513), in materials science as much as 18.4% (8,272), others 10.3% with Biochemistry, Genetics and Molecular Biology (818), Decision Sciences (788), Agricultural and Biological Sciences ( 571), Earth and Planetary Sciences (501), Multidisciplinary (431), Medicine (400), Social Sciences (348), Pharmacology, Toxicology and Pharmaceutics (297), Immunology and Microbiology (235), Economics, Econometrics and Finance (105 ). Meanwhile, countries with documents regarding the Taguchi method are India with 8,307 copies, Taiwan with 2,511 records, and Iran with 2,351 papers. As for the country, the least in Japan, which is 492 documents. From the results of this analysis, it can conclude that the Taguchi method plays a significant role and is needed in any research for quality development in many countries, especially in the engineering/manufacture field.